Hydrological Monitoring for Watershed Based Sustainable Water Management - Hasan, M.; Singh, A.; Bhattacharya, A.K. (Journal of Soil and Water Conservation, 2022)
The present study was undertaken with a view to explore and develop the concept of watershed based water management. For this exercise a high priority Karso watershed at Damodar valley corporation (D.V.C) Hazaribagh was selected which is gauged for silt monitoring. Attempt was made to investigate the possibility of meetingthe water demand from the water resource available within the watershed area. A new rating curve (Q=7.99d 6182) and velocity correction factor (Y=0.018+0.863x) were developed which can be adopted at the gauging station of the watershed for strengthening the hydrological data base. The monthly total and annual cumulative water availability (about 942 ha-m) and demand (about 718 ha-m) of the watershed were estimated. The water management plan for meeting the requirement of water during deficit period (from Jan. to July) was discussed. The study reveals an inadequacy of hydrological data base, appropriate analysis procedure and suggests on the need of research and up gradation of existing gauging set up in terms of data collection and management.